Aerosol Impacts on Storm Electrification and Lightning Discharges Under Different Thermodynamic Environments. Issue 8 (14th April 2023) - Sun, Mengyu; Qie, Xiushu; Mansell, Edward R.; Liu, Dongxia; Yair, Yoav; Fierro, Alexandre O.; Yuan, Shanfeng; Lu, Jingyu
Abstract: The impacts of aerosol and thermodynamics on electrification and lightning activities have been investigated in detail using the Weather Research and Forecasting Model coupled with a double‐moment microphysics parameterization and an explicit electrification lightning scheme. To obtain a varied combination of convective available potential energy (CAPE) values and aerosol concentrations, a sounding was modified consistently and initiated with five sets of aerosol concentrations that served as cloud condensation nuclei. The simulated electric processes respond to the varying dynamical and microphysical characteristics associated with the different CAPE and aerosol conditions. Under high CAPE circumstances, the augmentation of ice‐phase particle leads to the enhancement of non‐inductive charging primarily through the dynamic processes. Increased aerosol content further invigorates the electrification through microphysical processes. Elevated aerosol loading under low CAPE conditions increases cloud droplet and ice crystal numbers. Larger graupel particle size further leads to the enhanced electric intensity and lightning discharges. Plain Language Summary: A weather forecast model with an embedded lightning scheme was used to investigate the effects of aerosol and atmospheric conditions on electrification and lightning activity. Varied combinations of moisture and temperature profiles and aerosol concentration were considered in the simulations. The results showed that the electrification and lightning activity vary under different meteorological and aerosol conditions. Under high convective available potential energy (CAPE) conditions, the increased ice‐phase particle content leads to the enhancement of rebounding ice collisions mainly through the dynamic processes. Elevated aerosol loading under lower CAPE conditions invigorates lightning activity due to larger graupel particles participating in the thunderstorm electrification. Key Points: High convective available potential energy enhances non‐inductive charging due to augmentation of ice‐phase particle through dynamic process Elevated aerosol under low atmospheric instability conditions enhances lightning due to larger graupel participating in electrification An anomalous charge structure appears under polluted conditions, owing to positively charged graupel